Pengaruh Harga, Kualitas Layanan dan Café Atmosphere Terhadap Keputusan Pembelian di Tomoro Coffe pada Gen Z - Zidny Camelia; Kholifatur Rosyidah; M. Ashiful Ardan; Edita Rachma Kamila (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of price, service quality, and café atmosphere on the purchase decisions of Generation Z consumers at Tomoro Coffee. A quantitative approach was employed using a survey method with questionnaires distributed to 100 purposively selected respondents. The data were analyzed using multiple linear regression to examine both partial and simultaneous effects of the independent variables on purchase decisions. The results indicate that collectively, price, service quality, and café atmosphere significantly influence purchase decisions. However, individually, each variable does not have a significant effect, suggesting that Generation Z evaluates the overall experience in their decision-making process. These findings highlight the importance of a holistic strategy that combines competitive pricing, high-quality service, and a comfortable café atmosphere to attract and retain Generation Z consumers.